«Povitrya» Web-Based Software System for Operational Forecasting Atmospheric Pollution after Manmade Accidents in Ukraine - Kovalets, I.V.; Maistrenko, S.Yа.; Khalchenkov, O.V.; Zagreba, T.O.; Khurtsilava, K.V.; Anulich, S.M.; Bespalov, V.P.; Udovenko, O.I. (Science and Innovation, 2024)
Within the framework of this research, information technology for forecasting atmospheric pollutant transport following manmade accidents with emissions of hazardous matters has been developed. It is based on the integration of emission scenarios, atmospheric transport models of different complexity (from simplified local screening models to CALPUFF regional model), weather forecasting tools. Using freeware GIS and Web- technologies a pilot version of Povitrya webbased software and simulation system for analysis and forecast of air pollution in Ukraine caused by manmade disasters has been created and applied to simulation of air pollution following fire at oil storage facility in Vasylkiv, in June 2015.